Pemberdayaan Masyarakat Melalui Pengelolaan Sampah Plastik Menjadi Premium dan Solar Alternatif di Desa Buluagung Kecamatan Siliragung Kabupaten Banyuwangi - Nur Anim Jauhariyah; Nurul Inayah; Mahmudah Mahmudah; M. Alaika Nasrulloh (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2020)
The type of program of activities in this service is Community Empowerment Through Processing Plastic Waste into Premium and Alternative Solar in Buluagung Village, Siliragung District, Banyuwangi Regency, namely to process plastic waste processed into fuel oil by using a plastic catalyst machine as a village innovation, because the BUMDes "Panji Samudera "Has been facilitated by the village with a machine that can process plastic waste into fuel oil. Conclusions in this empowerment 1) The need to optimize community participation in utilizing plastic waste processing equipment into fuel oil (BBM) in Buluagung Village so that by utilizing plastic waste in addition to reducing plastic waste but also can bring a source of income for the surrounding community. 2) The need for refreshment in the BUMDES organizational structure 'Panji Samudera', due to lack of coordination and synchronization of communication with the community, causing the underutilization of the use of existing plastic catalyst machines.